Wave interaction with Floating platform of different shapes and supports using BEM approach - Shirkol, Anoop I.; Thuvanismail, Nasar (Journal of Naval Architecture and Marine Engineering, 2017)
Wave interaction with a floating thin elastic plate which can be used as floating platform is analyzed using Boundary Element Method (BEM) for different shapes such as rectangular, circular and triangular. Different support conditions are considered and the performance of the floating platform under the action of ocean waves is explored. The study is performed under the assumption of linearized water wave theory and the floating elastic plate is modelled based on the Euler-Bernoulli beam theory. Using Galerkins approach, a numerical model has been developed and the hydrodynamic loading on the floating elastic plate of shallow draft (thickness) is investigated. The wave forces are generated by the numerical model for the analysis of the floating plate. The resulting bending moment and optimal deflection due to encountering wave force is analysed. The present study will be helpful in design and analysis of the large floating platform in ocean waves.